1989
DOI: 10.2118/16744-pa
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Transient Testing of Water-Injection Wells

Abstract: Summary This paper presents an interpretation method for injectivity and falloff testing in a single-layer oil reservoir that is under waterflooding and develops analytical solutions for pressure and saturation distributions. The effects of relative permeability, wellbore storage, and skin are considered in these solutions. New field-dependent type curves for falloff tests, which exhibit features that do not appear in the currently available single-phase-flow type curves, are also presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 7 publications
0
48
0
1
Order By: Relevance
“…The governing flow equation generally becomes nonlinear and the system's effective hydraulic diffusivity is modified because of changes in mobility and total compressibility. In pressure interference tests, it is commonly assumed that injected fluid displaces the ambient fluid in a piston-like fashion such that the system consists of two radially stationary zones (or fluid banks): the saturation gradient within each fluid bank is negligible, and the mobility and total compressibility are relatively constant [Abbaszadeh and Kamal, 1989]. The application of HPT under two-phase flow conditions has been studied by Fokker and Verga [2011], who demonstrated that HPT can be used to monitor the evolution of effective parameters (i.e., effective mobility and total compressibility) under the assumptions of mild nonlinearity and slightly compressible fluids.…”
Section: Leak Detection In Carbon Sequestration Reservoirsmentioning
confidence: 99%
“…The governing flow equation generally becomes nonlinear and the system's effective hydraulic diffusivity is modified because of changes in mobility and total compressibility. In pressure interference tests, it is commonly assumed that injected fluid displaces the ambient fluid in a piston-like fashion such that the system consists of two radially stationary zones (or fluid banks): the saturation gradient within each fluid bank is negligible, and the mobility and total compressibility are relatively constant [Abbaszadeh and Kamal, 1989]. The application of HPT under two-phase flow conditions has been studied by Fokker and Verga [2011], who demonstrated that HPT can be used to monitor the evolution of effective parameters (i.e., effective mobility and total compressibility) under the assumptions of mild nonlinearity and slightly compressible fluids.…”
Section: Leak Detection In Carbon Sequestration Reservoirsmentioning
confidence: 99%
“…A thorough discussion on the applicability of analytical interpretation models, when different fluids are interacting in the reservoir, can be found in the technical literature (Abbaszadeh and Kamal, 1989;Beretta et al, 2007;Bourdet, 2002;Gunawan et al, 2002). Here it is worth recalling that, during the pressure fall-off subsequent to injection, only little changes in saturation are generally observed (Levitan, 2002), except in the presence of strong gravity and capillary effects, which will be discussed subsequently.…”
Section: Interpretation Of Injection Testsmentioning
confidence: 99%
“…A thorough discussion on the applicability of analytical interpretation models when different fluids are interacting in the reservoir can be found in the technical literature (Beretta et al, 2007;Gan et al, 2002;Abbaszadeh and Kamal, 1987;Bourdet, 2002). If the transition zone is neglected two zones with different mobilities and compressibilities are left.…”
Section: Production-reinjection Testingmentioning
confidence: 99%